Photocatalytic degradation of bisphenol a using hybrid oxalate pyrite/chitosan - R.Sugumaran, Rathashine; Hamidah, Abdullah; Jun Haslinda, Shariffuddin; Farhana, Aziz; Sambudi, Nonni; Ahmad Nazrul, Rosli (National Institute of Science Communication and Policy Research, 2025)
This study investigated the photocatalytic degradation of Bisphenol A (BPA) using a low-cost and environmentally friendly hybrid catalyst composed of oxalate-pyrite/chitosan. The effects of initial BPA concentration, catalyst dosage, and pH on the percentage of BPA degradation are examined. Additionally, both adsorption and photocatalytic degradation kinetics are evaluated. The findings revealed that BPA degradation is most effective at a lower initial concentration (5 mg/L) and at neutral pH (pH 7). Moreover, increasing the catalyst dosage led to a rise in photodegradation efficiency, although the improvement is not significant. The adsorption of BPA onto the hybrid oxalate-pyrite/chitosan catalyst conformed to the pseudo-second-order kinetic model, while the photocatalytic degradation followed pseudo-first-order reaction kinetics.